An Analysis of the Driving and Inhibiting Factors of Forests in Reducing Gadget Use Among Elementary School Students - Rani Darojah; Urip Tri Wijayanti; Faoyan Agus Furyanto; Cicilia Clara Devi Anggraini; Andry Mardian; Afifah Afifah; Rd. Deden Gumelar Nugraha; Inka Winarni Mufdhalifah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
The use of gadgets by elementary school children is a serious challenge that can disrupt their growth and development. Living environments, especially those close to nature such as forests, are believed to have the potential to distract children from using gadgets. This study aims to examine the driving and inhibiting factors of forest environments in reducing gadget use habits among students at SDN 3 Cikakak, Wangon District, Banyumas Regency. This study used a qualitative approach. Information was collected through questionnaires with all students at SDN 3 Cikakak, followed by data collection through in-depth interviews with parents, teachers, the principal, and elementary school supervisors. The results indicated that driving factors include the role of teachers and the science and science curriculum, support from children's social environment, positive family habits, and children's curiosity and enthusiasm for nature. Meanwhile, inhibiting factors include challenging geographical conditions, lack of security guarantees, children's habits that are not familiar with nature, low motivation, and children's continued dependence on gadgets. These findings emphasize the importance of a collaborative approach between schools, families, and parties concerned with forest environmental management to create effective intervention strategies to reduce gadget use among children.